Metanol – En lösning på framtida bränslekrav? - Boodaghian, David; Duracak, Armin (My University, 2015)
The shipping industry has long been described as a relatively environmentally friendly transportation option, in relation to the large volumes being transported. Therefore, minimal measures have been implemented to reduce the emissions of nitrogen and sulfur oxides. But as stricter emission regulations and new law from January 2015 take place, new solutions will be crucial for future shipping. In this study, a large number of aspects will be compared between methanol and LNG as a marine fuel. The focus of the study will be on environmental, financial and safety issues. As a basis for this study, these aspects are answered with the help of a literature survey, interview and a field trip. These combined are the source for what benefits there are to methanol as a future marine fuel. The result finds methanol as a strong candidate for being able to establish as a future marine fuel. We confirm, however, that LNG is already an established and proven fuel, making it a natural first choice. For the introduction of methanol as a marine fuel implementation and development is required. Engines are available but these are in the development and optimization phase. In conjunction with the new regulations regarding emissions rules, IMO (International Maritime Organistion) are working with a new regulatory framework regarding methanol as a marine fuel.
Keywords: Energi; Annan teknik; Transport; Energy; Other Engineering and Technologies; Transport